The impact of extension services on farming households in Western Kenya: A propensity score approach - Jean-Philippe Deschamps-Laporte (Örebro University School of Business, 2013)
The aim of this paper is to assess the impact of the adoption of technological packages in agriculture Kenya on the farming households, as promoted by the National Agriculture and Livestock Extension Programme (NALEP), a program run by the Government of Kenya. To this end, we collected data on beneficiaries through a survey of 1000 households in the district of Lugari, in Western Kenya. We use propensity score matching to compute the average treatment effect on the treated. We find evidence that: I) program beneficiaries changed their crop rotation practices; II) treated households increased their fertilizer dosage by 23.8%; IV) productivity per acre is not affected by the treatment; V) treated households also were less likely to store their surplus maize.
Keywords: Q12; Q13; Q16; 330; Agricultural Extension; Kenya; Propensity Score Matching; Maize; Fertilizer; Water Harvesting; Productivity